Survival and New Prognosticators in Metastatic Seminoma: Results From the IGCCCG-Update Consortium. Issue 14 (10th May 2021) - Beyer, Jörg; Collette, Laurence; Sauvé, Nicolas; Daugaard, Gedske; Feldman, Darren R.; Tandstad, Torgrim; Tryakin, Alexey; Stahl, Olof; Gonzalez-Billalabeitia, Enrique; De Giorgi, Ugo; Culine, Stéphane; de Wit, Ronald; et al.
Abstract : PURPOSE: The classification of the International Germ-Cell Cancer Collaborative Group (IGCCCG) has been a major advance in the management of germ-cell tumors, but relies on data of only 660 patients with seminoma treated between 1975 and 1990. We re-evaluated this classification in a database from a large international consortium. MATERIALS AND METHODS: Data on 2, 451 men with metastatic seminoma treated with cisplatin- and etoposide-based first-line chemotherapy between 1990 and 2013 were collected from 30 institutions or collaborative groups in Australia, Europe, and North America. Clinical trial and registry data were included. Primary end points were progression-free survival (PFS) and overall survival (OS) calculated from day 1 of treatment. Variables at initial presentation were evaluated for their prognostic impact. Results were validated in an independent validation set of 764 additional patients. RESULTS: Compared with the initial IGCCCG classification, in our modern series, 5-year PFS improved from 82% to 89% (95% CI, 87 to 90) and 5-year OS from 86% to 95% (95% CI, 94 to 96) in good prognosis, and from 67% to 79% (95% CI, 70 to 85) and 72% to 88% (95% CI, 80 to 93) in intermediate prognosis patients. Lactate dehydrogenase (LDH) proved to be an additional adverse prognostic factor. Good prognosis patients with LDH above 2.5× upper limit of normal had a 3-year PFS of 80% (95% CI, 75 to 84) and a 3-year OS of 92% (95% CI, 88 to 95) versus 92% (95% CI, 90 to 94) and 97% (95% CI, 96 to 98) in the group with lower LDH. CONCLUSION: PFS and OS in metastatic seminoma significantly improved in our modern series compared with the original data. The original IGCCCG classification retains its relevance, but can be further refined by adding LDH at a cutoff of 2.5× upper limit of normal as an additional adverse prognostic factor.